Food Webs and Food Sovereignty: Research Agenda for Sustainability - Charles Francis; Michelle Miller; Molly Anderson; Nancy Creamer; Michelle Wander; Jacob Park; Thomas A. Green; Brent H. McCown (Journal of Agriculture, Food Systems, and Community Development, 2016)
Future food production will be constrained by the scarcity of fossil fuel and fresh water as well as increasing intensity and unpredictability of weather events and climate changes. The assurance of food security and equity for many consumers is complicated by concentration of ownership of land and other production resources, as well as a global corporate food systems model that is driven by profit at the expense of people and the environment. To assess potential alternatives to the contemporary global food chain, well focused research is needed on local food production and food webs where small- and midscale family farms provide economic viability for rural communities and their regions. We suggest multiple and integrative research priorities in production, enterprise, and farm economics, environmental impacts of farming at different scales, and social and community consequences of value adding and economic multipliers in local food webs and systems as well as the structure of agriculture. Research into key questions on food security and how it relates to increased food sovereignty is clearly needed to assess creative food system alternatives for the future.